2016
DOI: 10.3390/ijms17101708
|View full text |Cite
|
Sign up to set email alerts
|

Potential Susceptibility Mutations in C Gene for Hepatitis B-Related Hepatocellular Carcinoma Identified by a Two-Stage Study in Qidong, China

Abstract: A two stage study was conducted to explore new potential mutations in the full genome of hepatitis B virus (HBV) on the progression of hepatocellular carcinoma (HCC) in Qidong, China. In stage 1, full genomes of HBV were compared between 30 HCC cases and 30 controls. In stage 2, an independent case–control study including 100 HCC cases and 100 controls was enrolled to verify the relationship between hot-spot mutations and HCC development. Furthermore, a longitudinal study was conducted on 11 HCC cases with ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…A separate longitudinal study demonstrated that six point mutations, including T1653, V1753, T1762, A1764, T1766, and A1768 were found to occur more frequently in cancer than in non-cancer patients. T1653 and V1753 were risk factors independent of the double mutation for liver cancer 37 . In the same cohort, Qu et al 38 observed that pre-S deletions and pre-S2 start codon mutations were independently associated with the development of liver cancer.…”
Section: Liver Cancer Preventionmentioning
confidence: 92%
“…A separate longitudinal study demonstrated that six point mutations, including T1653, V1753, T1762, A1764, T1766, and A1768 were found to occur more frequently in cancer than in non-cancer patients. T1653 and V1753 were risk factors independent of the double mutation for liver cancer 37 . In the same cohort, Qu et al 38 observed that pre-S deletions and pre-S2 start codon mutations were independently associated with the development of liver cancer.…”
Section: Liver Cancer Preventionmentioning
confidence: 92%